Polymeric hyaluronic acid structure, its method of manufacture and cosmetic composition containing same
Patent Information
- Application Number
- JP2024548753
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-23
- Filing Date
- 2023-02-17
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-02-17
AI Technical Summary
【0026】 本発明は、高分子量を同一に維持しながら、水素結合等のイオン結合のような分子内相互作用及び/またはイオンクラスター等の相互作用を活用した新しい構造のヒアルロン酸の構造体を製造することにより、粘度が著しく低下し、構造体に露出した表面が疎水性(hydrophobic)を有し、べたつきが減少し、皮膚適用時の使用感が改善され、高分子ヒアルロン酸の特徴である保湿性がさらに改善され、皮膚透過性もまた改善されるという利点がある。
Smart Images

Figure 2025506538000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0023658 dated February 23, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a polymeric hyaluronic acid structure, a method for producing the same, and a cosmetic composition containing the same, and more particularly to a polymeric hyaluronic acid structure in which the viscosity is reduced by applying shear stress to the polymeric hyaluronic acid, a method for producing the same, and a cosmetic composition containing the same. [Background technology]
[0003] Polymers are used in a wide range of industrial fields and have a wide range of applications. Polymers are broadly divided into synthetic polymers and natural polymers. Natural polymers are based on sugars such as hyaluronic acid and cellulose, and are materials with many applications, such as drug release and gel components in various cosmetic compositions.
[0004] Hyaluronic acid is a biopolymer present in the human body, and is abundantly distributed in the skin, vitreous body of the eye, synovial fluid, muscle, umbilical cord, cockscomb, etc., and performs various functions in various parts of the body. For example, hyaluronic acid prevents the invasion of bacteria and other organisms into the human body, and acts as a lubricant to facilitate bodily movements. Hyaluronic acid is separated and extracted from animal tissues and raw materials, and has a structure in the form of a sodium salt. Hyaluronic acid promotes collagen synthesis to improve skin density, and has a water adsorption capacity of up to 1,000 times its weight, and has a strong moisturizing effect, so it has been developed in many cosmetics, quasi-drugs, and biomaterials.
[0005] Cosmetic raw materials in which biopolymer solutions are used have various physical properties that determine the flow of the solution, and it is known that the flow characteristics of the polymer solution, such as viscosity, elasticity (G'), viscosity (G"), complex viscosity (G*) and phase angle (P / A), affect the feel when used and the skin permeability. For example, if the viscosity of the polymer solution is too low, it lacks elasticity and feels like it flows like water, whereas if the viscosity of the polymer solution is too high, it is very sticky and has too strong elasticity, making it difficult to apply to the skin or impossible to apply at all.
[0006] In the case of conventional cosmetic formulations containing hyaluronic acid, most of them are used at low concentrations of 0.01% to 0.02% due to the high viscosity and high price of hyaluronic acid. In the case of products containing hyaluronic acid at a high concentration of 0.05% or more, it can only be used in the form of essence or emulsion. Generally, most functional cosmetic raw materials can be expected to perform their functions only when they are contained in a formulation at 2% or more, but the amount of hyaluronic acid contained in most conventional cosmetic formulations is extremely small, about 0.01 to 0.02%, so the effect of hyaluronic acid itself cannot be obtained. If hyaluronic acid is contained at 1% or more to maximize the moisturizing effect caused by hyaluronic acid, there are problems such as a significant decrease in the feeling of use due to phenomena such as the skin being pulled during use due to the increase in viscosity, or a film-like residue remaining on the skin surface over time after application. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 2021-0015377 (2021.02.10), Method for producing low-viscosity hyaluronic acid Summary of the Invention [Problem to be solved by the invention]
[0008] The technical problem to be solved by the present invention is to provide a polymeric hyaluronic acid structure, a method for producing the same, and a cosmetic composition containing the same, and more specifically, to provide a polymeric hyaluronic acid structure having a reduced viscosity without reducing the molecular weight by applying shear stress to the polymeric hyaluronic acid, a method for producing the same, and a cosmetic composition containing the same.
[0009] The technical problems that the present invention aims to achieve are not limited to the technical problems mentioned above, and other technical problems not mentioned above will be clearly understood by a person having ordinary skill in the art to which the present invention pertains from the following description. [Means for solving the problem]
[0010] In order to achieve the above technical objectives, the polymeric hyaluronic acid structure according to one aspect of the present invention may have a single polymer chain.
[0011] In one embodiment of the present invention, the single polymer chain may form an ionic aggregate.
[0012] In one embodiment of the present invention, the ion association may have a spherical structure with a diameter of 1 to 20 nm.
[0013] In one embodiment of the present invention, the molecular weight of the polymeric hyaluronic acid is 5.0×10 4 ~5.0×10 6 It may be in the g / mol range.
[0014] In one embodiment of the present invention, the structure may be manufactured by applying shear stress to a solution containing hyaluronic acid, which is a precursor of the structure.
[0015] In one embodiment of the present invention, the shear stress may be applied by passing a solution containing hyaluronic acid, which is a precursor of the structure, through a column filled with silica.
[0016] In one embodiment of the present invention, the shear stress may be applied by passing a solution containing hyaluronic acid, which is a precursor of the structure, through one or more filter papers.
[0017] In one embodiment of the present invention, the filter paper may be arranged by stacking two or more filter papers.
[0018] In one embodiment of the present invention, the shear stress may be applied by applying ultrasonic waves to a solution containing hyaluronic acid, which is a precursor of the structure.
[0019] In one embodiment of the present invention, the solution containing the structure is 5.0×10 4 ~5.0×10 6 When the molecular weight is g / mol and the concentration is 0.1 to 2.0%, the viscosity of the solution containing the structure may be 10 to 700 cP.
[0020] In one embodiment of the present invention, when the molecular weight and concentration of the structure and the hyaluronic acid that is the precursor of the structure are the same, the ratio of the viscosity (a) of the solution containing the structure to the viscosity (b) of the solution containing the hyaluronic acid that is the precursor of the structure, a / b, may be 0.10 to 0.99.
[0021] In one embodiment of the present invention, the contact angle of the solution containing the polymeric hyaluronic acid structure on the hydrophilic glass surface may be 20° to 30°.
[0022] In one embodiment of the present invention, the contact angle of the solution containing the polymeric hyaluronic acid structure on the hydrophobic glass surface may be 80° to 100°.
[0023] In one embodiment of the present invention, the intrinsic viscosity of the solution containing the polymeric hyaluronic acid structure is 0.1 to 2.0 m 3 / kg.
[0024] In one embodiment of the present invention, a cosmetic composition including the polymeric hyaluronic acid structure may be provided.
[0025] In one embodiment of the present invention, a method for producing a polymeric hyaluronic acid structure can be provided, in which the polymeric hyaluronic acid structure is produced by applying shear stress to a solution containing hyaluronic acid, which is a precursor of the structure. Effect of the Invention
[0026] The present invention provides a novel structure of hyaluronic acid that utilizes intramolecular interactions such as ionic bonds, including hydrogen bonds, and / or interactions such as ion clusters while maintaining the same high molecular weight. This has the advantages of significantly reducing viscosity, making the surface exposed to the structure hydrophobic, reducing stickiness, improving the feel when applied to the skin, further improving the moisturizing properties that are characteristic of high molecular weight hyaluronic acid, and also improving skin permeability.
[0027] Due to these advantages, the polymeric hyaluronic acid structure of the present invention can be used in a variety of cosmetic compositions. [Brief description of the drawings]
[0028] [Figure 1] FIG. 2 is a diagram showing a polymer chain of hyaluronic acid, which is a precursor of a structure according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing a single polymer chain of hyaluronic acid, which is a precursor of a structure according to one embodiment of the present invention. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of an aqueous solution including a structure according to an embodiment of the present invention; [Figure 4] 1 is a scanning electron microscope (SEM) photograph of an aqueous solution including a structure according to an embodiment of the present invention; [Diagram 5]1 is a transmission electron microscope (TEM) photograph of hyaluronic acid, which is a precursor of a structure according to an embodiment of the present invention. [Figure 6] FIG. 1 is a diagram showing a comparison of HPLC measurement results according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Generally, polymers have a long chain structure with regular repeating units formed by chemical reactions of monomer molecules, unlike the structure of molecules with low molecular weight. The structure of polymers with long chains exists in a solid state, or has a twisted chain structure when in a liquid state.
[0030] In very dilute polymer solutions, the viscosity is related to the volume, which is well known from Einstein's equation and can be shown as follows:
number
[0031] The volume of a polymer solution per unit mass is larger as the molecular weight is larger, as the affinity between the solvent and the polymer is larger, and as the repulsive force between unit chain structures is larger.
[0032] Furthermore, when the concentration of a polymer solution is high, the chains penetrate each other and form a very large continuous structure, whereas when the concentration of the polymer is low, the interaction between the chains decreases.
[0033] Unlike ionic polymers, each chain of which exists independently, hyaluronic acid polymers in aqueous solution are known to form twin helix structures in which two chains are bundled together. This is sometimes called twin helix or macromolecular crowding. Figure 1 shows a schematic diagram of two chains of hyaluronic acid polymers intertwined with each other to form a twin helix structure.
[0034] In general, high molecular weight hyaluronic acid promotes collagen synthesis, has a longer residual time in the skin, and has excellent moisturizing effects compared to low molecular weight hyaluronic acid. However, due to the large molecular weight of hyaluronic acid, there are problems such as stickiness when applied to the skin, poor usability, and difficulty in penetrating into the skin. In order to solve these problems, many studies are being conducted to adjust the viscosity of the polymer solution.
[0035] However, such viscosity control methods have limitations in that they do not maintain the polymer characteristics of hyaluronic acid, such as reducing the viscosity of the polymer solution by inducing hydrolysis of the polymer chain of hyaluronic acid through pH control, addition of a catalyst, etc., thereby reducing the molecular weight.
[0036] In order to solve the above problems, the present inventors have confirmed that a pair of polymer chains of a polymeric hyaluronic acid having a very high viscosity is transformed into a single polymer chain (single helix) by applying a high shear stress, and an ion association is formed due to the intramolecular interaction between the single polymer chains.
[0037] This resulted in a decrease in the volume of the polymeric hyaluronic acid chains, which in turn reduced the volume of the polymeric hyaluronic acid in solution, thereby significantly reducing the viscosity.
[0038] In the following, first, a method for producing a polymeric hyaluronic acid structure according to one embodiment of the present invention will be described, and then the polymeric hyaluronic acid structure will be specifically described.
[0039] Method for producing polymeric hyaluronic acid structures The term "polymeric hyaluronic acid structure" as used herein means a structure having a single polymer chain structure formed by applying shear stress to polymeric hyaluronic acid having a pair of polymer chain structures.
[0040] The term "precursor" as used herein refers to a precursor or precursor used to generate the polymeric hyaluronic acid structure according to the present invention, i.e., the precursor of the polymeric hyaluronic acid structure according to the present invention refers to hyaluronic acid having a paired polymer chain structure to which no shear stress is applied.
[0041] The polymeric hyaluronic acid structure according to an embodiment of the present invention can be prepared by applying shear stress to a solution containing hyaluronic acid, which is a precursor of the structure.
[0042] The shear stress applied to the solution containing hyaluronic acid, which is the precursor of the structure, may be either mechanical shear stress or ultrasonic application.
[0043] The mechanical shear stress may be applied by passing the solution through a silica-filled column or filter paper. The mechanical shear stress will be described in detail below.
[0044] According to one embodiment of the present invention, the mechanical shear stress may be applied by passing a solution containing hyaluronic acid, which is a precursor of the structure, through a column filled with silica. When the solution containing hyaluronic acid passes through a column filled with silica or the like, the hyaluronic acid, which is a precursor of the structure, is subjected to very high shear stress by passing through a physically narrow area.
[0045] The silica may be spherical or angular, but is not limited to that morphology.
[0046] The size of the silica may be 0.01-0.50 mm, 0.05-0.40 mm, or 0.06-0.30 mm. If the size of the silica is less than 0.01 mm or exceeds 0.50 mm, the structure may not change even if the solution containing the hyaluronic acid passes through a column filled with silica, since no shear stress is applied.
[0047] The lower part of the column packed with silica may be subjected to a negative pressure of 0.1 bar to 1.0 bar or 0.2 bar to 0.9 bar. If the negative pressure applied to the lower part of the column packed with silica is less than 0.1 bar, the time required for the solution containing hyaluronic acid to pass through the column may increase, and the manufacturing time of the polymeric hyaluronic acid structure according to the present invention may be delayed. If the negative pressure applied to the lower part of the column packed with silica exceeds 1.0 bar, the time required for the solution containing hyaluronic acid to pass through the column may be shortened, and the manufacturing time of the polymeric hyaluronic acid structure according to the present invention may be shortened, but an additional pump equipment is required, which may increase the manufacturing cost.
[0048] According to another embodiment of the present invention, the mechanical shear stress may be applied by passing the solution containing the hyaluronic acid through one or more filter papers, whereby the hyaluronic acid, which is the precursor of the structure, is subjected to very high shear stress by passing through a physically narrow area.
[0049] The filter paper may be one filter paper or two or more filter papers. When the filter paper is two or more filter papers, the filter papers may be stacked. When the filter paper is two or more filter papers, it may provide a higher shear stress than a single filter paper.
[0050] The pore size of the filter paper may be 0.1-5.0 microns or 0.3-4.5 microns. If the pore size of the filter paper is less than 0.1 microns, the amount of the solution containing hyaluronic acid passing through or filtering through the filter paper is too small, which may reduce the production speed of the polymeric hyaluronic acid structure according to the present invention. If the pore size of the filter paper is more than 5.0 microns, the solution containing hyaluronic acid may simply pass through the filter paper, and shear stress may not be applied effectively.
[0051] The shear stress may be applied by using ultrasonic waves. The application of ultrasonic waves will be specifically described below.
[0052] According to one embodiment of the present invention, the shear stress may be applied by applying ultrasonic waves to a solution containing the hyaluronic acid.
[0053] When the ultrasonic waves are applied to a solution containing the hyaluronic acid, pressure waves are generated, and the pressure waves can apply shear stress to the hyaluronic acid, which is the precursor of the structure.
[0054] The intensity of the applied ultrasonic waves may be 200 J / sec to 800 J / sec or 400 J / sec to 600 J / sec.
[0055] The energy applied per volume of the applied ultrasound can be calculated by ultrasound intensity (J / sec) x application time (sec) / measurement volume (ml).
[0056] According to one embodiment of the present invention, the energy of the ultrasonic waves applied to the solution containing hyaluronic acid per volume may be 100J / ml to 90kJ / ml. If the energy of the ultrasonic waves is less than 100J / ml, sufficient shear stress is not applied to the solution containing hyaluronic acid, and it may be difficult to form a structure. If the energy of the ultrasonic waves exceeds 90kJ / ml, excessive heat is applied to the solution containing hyaluronic acid, and it may be difficult to form a structure.
[0057] The ultrasonic wave can be applied at 10°C to 80°C for 10 seconds to 60 minutes. When the ultrasonic wave is applied at a temperature below 10°C, the solution containing hyaluronic acid does not change, and when the ultrasonic wave is applied at a temperature above 80°C, a phase change occurs in the solution containing hyaluronic acid, which may make it difficult to form the polymeric hyaluronic acid structure according to the present invention. In addition, when the ultrasonic wave is applied for less than 10 seconds, the solution containing hyaluronic acid does not change, and when the ultrasonic wave is applied for a time exceeding 60 minutes, the structure in the solution containing hyaluronic acid is deformed, making it impossible to form the polymeric hyaluronic acid structure according to the present invention.
[0058] According to another embodiment of the present invention, the method of applying shear stress can be achieved by combining a silica-filled column with an ultrasonic generator. The silica-filled column can be disposed inside the ultrasonic generator, or the silica-filled column and the ultrasonic generator can be disposed separately and continuously.
[0059] For example, the solution containing hyaluronic acid can be poured into the column packed with silica, and then the column can be placed in an ultrasonic generator to apply ultrasonic waves.Also, the solution containing hyaluronic acid can be applied with ultrasonic waves, and then the solution can be passed through the column packed with silica.
[0060] Polymeric hyaluronic acid structure The polymeric hyaluronic acid structure of the present invention can be produced by the above-mentioned production method. Specifically, the polymeric hyaluronic acid structure can have the form of a single polymer chain by applying shear stress to the precursor hyaluronic acid of the structure.
[0061] The single polymer chain may have a structure that includes the chemical structure of hyaluronic acid as shown in FIG. 2. The chemical structure of hyaluronic acid includes one carboxyl anion (-COO) for every two cyclic hexoses. - ) groups.
[0062] The distance between the single polymer chains becomes short, and an ionic aggregate can be formed by intramolecular interaction and / or interaction such as ion cluster. The intramolecular interaction can be performed via intramolecular hydrogen bond, ionic bond, etc. The interaction such as ion cluster can be performed by carboxyl anion (-COO δ- ) and sodium cation (Na δ+ This can be achieved through interactions between the partial charges of
[0063] The ion associate can include a spherical structure as shown in Figures 3 and 4. The ion associate can include a spherical structure having a diameter of 1 to 20 nm, 2 to 18 nm, or 3 to 16 nm due to the intramolecular interaction or the interaction such as an ion cluster.
[0064] On the other hand, hyaluronic acid, which is a precursor of the structure according to the present invention, has a general polymer chain structure and does not contain ion associates having a spherical structure. Figure 5 is a TEM photograph of hyaluronic acid, which is a precursor of the structure according to the present invention, in which only lines are observed as traces generated during the freezing process for TEM photography of the hyaluronic acid, and the shape of ion associates having a spherical structure is not observed.
[0065] Molecular weight of polymeric hyaluronic acid structures The molecular weight of the polymeric hyaluronic acid structure according to the present invention is 5.0×10 4 ~5.0×10 6 It may also be g / mol.
[0066] The molecular weight of the polymeric hyaluronic acid structure according to the present invention is the same as that of the precursor hyaluronic acid of said structure.That is, even if shear stress is applied to the solution containing the precursor hyaluronic acid of said structure to produce the polymeric hyaluronic acid structure, it can produce a structure that maintains the same molecular weight as the precursor hyaluronic acid of said structure before shear stress is applied, and has low viscosity.
[0067] In FIG. 6, (a) is a graph showing a molecular weight measurement curve of sodium hyaluronate, which is a precursor of the structure according to the present invention, and (b) is a graph showing a molecular weight measurement curve of the polymer hyaluronan structure according to the present invention.
[0068] As shown in Fig. 6, it was confirmed that the molecular weight measurement curve of the hyaluronic acid precursor of the structure according to the present invention and the molecular weight measurement curve of the polymeric hyaluronic acid structure according to the present invention are almost the same without any change.Therefore, the polymeric hyaluronic acid structure according to the present invention can provide a polymeric hyaluronic acid structure with reduced viscosity without reducing the molecular weight even when shear stress is applied to the hyaluronic acid precursor of the structure.
[0069] The polymeric hyaluronic acid structure according to the present invention maintains the effects of high molecular weight hyaluronic acid, such as promotion of collagen synthesis and excellent moisturizing power, while lowering the viscosity to eliminate stickiness when applied to the skin, improving the feel when used, and improving penetration into the skin.
[0070] Viscosity of polymeric hyaluronic acid structures 5.0×10 4 ~5.0×10 6The viscosity of a solution containing a polymeric hyaluronic acid structure having a molecular weight of g / mol and a concentration of 0.1 to 2.0% may be 10 to 700 cP or 15 to 680 cP.
[0071] According to one embodiment of the present invention, when shear stress is applied to a solution containing polymeric hyaluronic acid, which is a precursor of the polymeric hyaluronic acid structure, the physical structure of the hyaluronic acid is transformed from a twin helix structure to a single polymer chain, thereby reducing the viscosity and maintaining the high molecular weight of the hyaluronic acid.
[0072] The reason why the viscosity of the solution containing the polymeric hyaluronic acid structure according to the present invention is significantly reduced is that the application of shear stress to the solution containing hyaluronic acid, which is the precursor of the structure, results in the formation of the single polymer chain, and the formation of ionic associations within the single polymer chain, thereby reducing the volume of the polymer chain, and thus reducing the volume of the polymeric hyaluronic acid in the solution.
[0073] According to one embodiment of the present invention, when the molecular weight and concentration of the polymeric hyaluronic acid structure and the hyaluronic acid precursor of the structure are the same, the ratio of the viscosity (a) of the solution containing the structure to the viscosity (b) of the solution containing the hyaluronic acid precursor of the structure, a / b, may be 0.10 to 0.99.
[0074] Contact angle of polymeric hyaluronic acid structures The contact angle of a solution containing the polymeric hyaluronic acid structure produced according to one embodiment of the present invention may be 20° to 30° on a hydrophilic glass surface, and 80° to 100° on a hydrophobic glass surface.
[0075] The contact angle may be measured by the sessile drop method for measuring a static contact angle, or the tilting drop method, captive drop method, Wilhelmy plate method, or the like for measuring a dynamic contact angle, and preferably by the sessile drop method.
[0076] The hydrophilic glass surface may be a glass surface containing an untreated silica material.
[0077] The hydrophobic glass surface may be a glass surface comprising a material coated with a Teflon emulsion.
[0078] Intrinsic viscosity of polymeric hyaluronic acid structures Intrinsic viscosity refers to the volume per unit mass of a polymer in the absence of viscous effects in the polymer solution.
[0079] The intrinsic viscosity can be measured by measuring the aqueous solution to be measured according to the concentration, calculating the reduced viscosity, and extrapolating the reduced viscosity at a concentration of 0. The intrinsic viscosity can be calculated using the following Equation 4.
[0080] The following formula 2 is a formula for calculating the relative viscosity, and the following formula 3 is a formula for calculating the reduced viscosity (where η is the viscosity of the solution, η0 is the viscosity of the solvent, and c is the concentration of the solution). Generally, the concentration (c) of the solution is expressed in units of (w / v), which means that η red This is because the physical meaning of is the volume per unit weight of the polymer in the solution. The reduced viscosity is plotted against the concentration, and the intercept obtained by linearly extrapolating the point where the concentration is 0 as described above is the intrinsic viscosity.
[0081]
number
[0082]
number
[0083]
number
[0084] The intrinsic viscosity of the solution containing the polymeric hyaluronic acid structure according to the present invention can be calculated based on the above-mentioned formulas 2 to 4. The specific intrinsic viscosity measurement value of the solution containing the polymeric hyaluronic acid structure according to the present invention is described in the following Experimental Example 9.
[0085] Cosmetic composition containing polymeric hyaluronic acid structure According to one embodiment of the present invention, a cosmetic composition including the polymeric hyaluronic acid structure can be provided.
[0086] The cosmetic composition may include the structural features of the polymeric hyaluronic acid according to the present invention.
[0087] The explanation of the structure of the polymeric hyaluronic acid is the same as that described above.
[0088] The cosmetic composition of the present invention can be prepared in the form of a general emulsion or solubilized formulation. The emulsion formulation can be a nutritional lotion, cream, essence, etc., and the solubilized formulation can be a softening lotion. In addition to the cosmetic composition of the present invention, it can be prepared in the form of a topical or systemic application auxiliary that is commonly used in the cosmetics field by containing a dermatologically acceptable medium or base.
[0089] Suitable cosmetic formulations may be provided, for example, in the form of a solution, a gel, a solid or pasty anhydrous product, an emulsion obtained by dispersing an oily phase in an aqueous phase, a suspension, a microemulsion, a microcapsule, a cream, a skin, a lotion, a powder, an ointment, a spray, or a conceal stick.
[0090] In addition to the solution containing the polymeric hyaluronic acid structure, the cosmetic composition of the present invention may further contain auxiliary agents commonly used in the fields of cosmetology or dermatology, such as fatty substances, organic solvents, solubilizers, thickening and gelling agents, softeners, antioxidants, suspending agents, stabilizers, foaming agents, fragrances, surfactants, water, ionic or non-ionic emulsifiers, fillers, sequestering and chelating agents, preservatives, vitamins, blocking agents, moisturizing agents, essential oils, dyes, pigments, hydrophilic or lipophilic active agents, or any other ingredients commonly used in cosmetics. The above ingredients may be incorporated in amounts commonly used in the field of cosmetics.
[0091] The cosmetic composition of the present invention may be prepared in any dosage form commonly used in the art, for example, cosmetics such as astringent lotion, softening lotion, nutritious lotion, various creams, essence, pack, foundation, etc., cleansing, facial cleanser, soap, treatment, serum, etc. Specific dosage forms of the cosmetic composition of the present invention include skin lotion, skin softener, skin toner, astringent, lotion, milk lotion, moisture lotion, nutritious lotion, massage cream, nutritious cream, moisture cream, hand cream, essence, nutritious essence, pack, soap, shampoo, cleansing foam, cleansing lotion, cleansing cream, body lotion, body cleanser, emulsion, pressed powder, loose powder, eye shadow, etc. EXAMPLES
[0092] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments set forth herein.
[0093] Fabrication of polymeric hyaluronic acid structures [Example 1] Molecular weight is 1.2 x 10 60.5 g of sodium hyaluronate (Lyphar, China) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.5% (w / v).
[0094] A column with a diameter of 5.2 cm and a height of 6 cm was filled with 15 g of silica (Merck's silica 60), and 100 g of distilled water was poured into the column to crush the silica in the column, preparing a column filled with silica. Then, the prepared aqueous solution of sodium hyaluronate with a concentration of 0.5 (w / v)% was slowly poured into the column filled with silica. A negative pressure of about 0.2 bar was applied to the bottom of the column filled with silica, and the aqueous solution of sodium hyaluronate was passed through the column (passing time: about 10 minutes), to prepare an aqueous solution containing a polymeric hyaluronate structure.
[0095] [Example 2] Molecular weight is 1.2 x 10 6 0.5 g of sodium hyaluronate (Lyphar, China) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.5% (w / v).
[0096] A filter paper (Hyundai Micro) with a pore size of 3 μm was attached to the filtration surface of a Buchner funnel, and then a negative pressure of about 0.2 bar was applied to the bottom of the Buchner funnel using a vacuum device to filter the prepared aqueous solution of sodium hyaluronate (filtration time: about 40 seconds) to prepare an aqueous solution containing a polymeric hyaluronate structure.
[0097] [Example 3] A filter paper having 3 μm pores (Hyundai Micro), a filter paper having 1.0 μm pores, and a filter paper having 0.45 μm pores were stacked on a Buchner funnel and adhered to the filtration surface, and then a negative pressure of about 0.2 bar was applied to the bottom of the Buchner funnel using a vacuum device, and the aqueous solution of hyaluronic acid sodium salt prepared in Example 2 was repeatedly filtered six times, but an aqueous solution containing a polymeric hyaluronic acid structure was prepared in the same manner as in Example 2.
[0098] [Example 4] Molecular weight is 1.2 x 10 6 1 g of sodium hyaluronate (Lyphar, China) was placed in a measuring cylinder and distilled water was added to bring the total volume to 250 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.4% (w / v).
[0099] The prepared hyaluronic acid sodium salt aqueous solution was placed in an ultrasonic generator (KODO Technical Research Co., Ltd. JAC-5020, Korea) and ultrasonic waves were applied at 25° C. for 30 minutes to prepare an aqueous solution containing a polymeric hyaluronic acid structure.
[0100] [Example 5] Molecular weight is 3.0 x 10 4 g / mol, 5.0×10 4 g / mol, 1.0×10 5 g / mol and 9.0×10 5 An aqueous solution containing a polymeric hyaluronic acid structure was prepared in the same manner as in Example 4, except that g / mol of sodium hyaluronic acid was used.
[0101] [Comparative Example 1] Molecular weight is 1.2 x 10 60.5 g of sodium hyaluronate (Lyphar, China) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.5% (w / v).
[0102] Experimental Example 1: Viscosity Comparison of Examples 1, 2 and Comparative Example 1 The viscosities of the aqueous solutions of Examples 1 and 2 and Comparative Example 1 were measured at 25° C. using a viscometer (Brookfield DV2T viscometer). The measured viscosities are shown in Table 1 below.
[0103] [Table 1]
[0104] From the results in Table 1, it was confirmed that the viscosity of the aqueous solution containing the polymeric hyaluronic acid structure prepared in Examples 1 and 2 was significantly lower than the viscosity of the sodium hyaluronic acid solution, which is the precursor of the structure prepared in Comparative Example 1.
[0105] From these results, it was confirmed that when a specific shear stress is applied to hyaluronic acid, the twin helix structure of hyaluronic acid is transformed into a single helix structure, and a polymeric hyaluronic acid structure is produced in which ionic aggregates are formed within the single polymer chain. The reason why the viscosity of the solution containing the polymeric hyaluronic acid structure according to the present invention is significantly reduced is because the volume of the polymer chain can be reduced by forming ionic aggregates within the single polymer chain, and therefore the volume of the polymeric hyaluronic acid in the solution is reduced.
[0106] Experimental Example 2: Viscosity measurement depending on the concentration of the aqueous solutions of Example 1 and Comparative Example 1 Distilled water was added to the 0.5% (w / v) aqueous solutions prepared in Example 1 and Comparative Example 1 to prepare aqueous solutions having various concentrations. The concentrations of the aqueous solutions were adjusted using only distilled water without adding other salts or adjusting the pH. The measured viscosities are shown in Table 2 below.
[0107] [Table 2]
[0108] From the results in Table 2, it was confirmed that, in general, the viscosity of the polymeric hyaluronic acid aqueous solution increases significantly as the concentration increases (Comparative Example 1), whereas the aqueous solution containing the polymeric hyaluronic acid structure according to the present invention maintains a low viscosity even when the concentration increases.
[0109] Experimental Example 3: Viscosity measurement of aqueous solutions of Examples 4 and 5 according to molecular weight The viscosity of the structures prepared in Examples 4 and 5 was measured. This allows the viscosity ratio before and after ultrasonic application to be compared for hyaluronic acid structures with various molecular weights. At this time, the concentration of the prepared hyaluronic acid sodium salt is 0.4% (w / v). The measured viscosity is shown in Table 3 below.
[0110] [Table 3]
[0111] From the results in Table 3, it was confirmed that the change in viscosity before and after the application of ultrasound increases as the molecular weight of sodium hyaluronate increases. 4 ~2.0×10 6 It was confirmed that the viscosity reduction effect before and after ultrasonic application was large in hyaluronic acid structures with molecular weights in the g / mol range.
[0112] Experimental Example 4: Viscosity measurement of the aqueous solution of Example 4 depending on ultrasonic application time The viscosity of the aqueous solution containing the polymeric hyaluronic acid structure prepared in Example 4 was measured according to the ultrasonic application time. The measured viscosities are shown in Table 4 below.
[0113] [Table 4]
[0114] From the results in Table 4, it was confirmed that the change in viscosity before and after ultrasonic application for sodium hyaluronate of the same molecular weight and concentration increases as the ultrasonic application time increases. 6 It was confirmed that in an aqueous solution containing a hyaluronic acid structure having a molecular weight of g / mol and a concentration of 0.4% (w / v), the longer the ultrasound application time, the greater the effect of reducing viscosity before and after ultrasound application.
[0115] Experimental Example 5: Measurement of molecular weight change before and after ultrasonic application Molecular weight is 1.2 x 10 6 g / mol of sodium hyaluronate (0.02 g) was placed in a graduated cylinder, and 0.9% (w / v) NaCl was added and dissolved to make a total volume of 20 mL to prepare a sodium hyaluronate aqueous solution. 0.8 mL of the aqueous solution was taken, and 0.1 M Na2SO4 was added to make a solution with a total volume of 10 mL. Then, distilled water was added to the solution to dilute the concentration by 2 times, and a sample for analysis by High-Performance Liquid Chromatography (HPLC) was prepared.
[0116] The solution prepared in the same manner as in Experimental Example 5 was placed in an ultrasonic generator, and ultrasonic waves were applied to prepare an aqueous solution containing a polymeric hyaluronic acid structure. Using the aqueous solution prepared above, a sample for gel permeation chromatography (GPC) measurement was prepared.
[0117] For the concentration and molecular weight analysis of the HPLC analysis sample and GPC measurement sample, HPLC (e2695, waters) and GPC column (OHPak SB-802.5 HQ 8.0×300 mm, 6 um, Shodex) were used. 0.1 M sodium sulfate (Na2SO4) aqueous solution prepared by dissolving 14.2 g of sodium sulfate anhydrous (DAEJUNG) in 1 L of purified water was used as the mobile phase. The column temperature was maintained at 40° C., the oven temperature at 25° C., 100% 0.1 M sodium sulfate (Na2SO4) was added, and the sample was stabilized in the oven at a flow rate of 1.0 mL / min for 1 hour. Then, the sample was filtered with a syringe filter (material: PVDF, 0.2 μm, Φ 13 mm), and 20 μL was injected into the GPC column and analyzed at UV 210 nm wavelength for 16 minutes.
[0118] In FIG. 6, (a) is a diagram showing the molecular weight of sodium hyaluronate, which is a precursor of the structure according to the present invention, and (b) is a diagram showing the molecular weight of the polymeric hyaluronan structure according to the present invention.
[0119] It was confirmed that the molecular weight measurement curve of the hyaluronic acid precursor of the structure according to the present invention and the molecular weight measurement curve of the polymeric hyaluronic acid structure according to the present invention were almost identical with no change.
[0120] Experimental Example 6: Evaluation of skin applicability and absorbency of the aqueous solutions of Examples 1 and 2 and Comparative Example 1 The aqueous solution containing the hyaluronic acid structure according to the present invention can be used in various fields. For example, the aqueous solution containing the hyaluronic acid structure can be used as a cosmetic composition.
[0121] Therefore, a sensory evaluation was carried out on the sensation when the aqueous solutions of Examples 1 and 2 and Comparative Example 1 were applied to the skin. The application property to the skin and the absorbency of the aqueous solution according to the present invention were evaluated on 10 males and 10 females (total of 20 subjects).
[0122] The responses regarding skin spreadability and absorbency were defined into three grades as shown in Tables 5 and 6 below: skin spreadability (poor / fair / excellent) and absorbency (poor / fair / excellent).
[0123] [Table 5]
[0124] [Table 6]
[0125] As shown in Tables 5 and 6, the aqueous solution containing the hyaluronic acid structure according to the present invention exhibited excellent spreadability and absorbency.
[0126] Experimental Example 7: Evaluation of Moisture Retention of Aqueous Solutions of Examples 1 and 2 and Comparative Example 1 The water retention capacity of the aqueous solutions of Examples 1 and 2 and Comparative Example 1 was measured, and the skin moisturizing degree was evaluated.
[0127] 1 g of each sample was taken and placed in a 10 cc vial and left at 25° C. for 1 hour, after which the change in weight was measured. The results are shown in Table 7 below.
[0128] [Table 7]
[0129] In Table 7, it was confirmed that the aqueous solution of sodium hyaluronate (Example 1) that passed through a column filled with silica and the aqueous solution of sodium hyaluronate (Example 2) that passed through a filter had a lower viscosity than the aqueous solution of sodium hyaluronate (Comparative Example 1) that did not receive shear stress, but had a smaller weight change.Therefore, it was found that the aqueous solution containing the structure of hyaluronate according to the present invention has a lower viscosity and is excellent in moisturizing power.
[0130] Experimental Example 8: Measurement of contact angles of aqueous solutions of Examples 1 and 2 and Comparative Example 1 The contact angles were measured for the aqueous solutions prepared in Examples 1 and 2 and Comparative Example 1. The contact angles were measured on a hydrophilic glass surface and a hydrophobic glass surface, respectively. The measured contact angles are shown in Table 8 below.
[0131] [Table 8]
[0132] In Table 8, the contact angles of the aqueous solutions prepared in Examples 1 and 2 on the hydrophilic glass surface were larger than that of Comparative Example 1, while the contact angles of the aqueous solutions prepared in Examples 1 and 2 on the hydrophobic glass surface were smaller than that of Comparative Example 1. This indicates that the aqueous solutions prepared in Examples 1 and 2 are relatively lipophilic.
[0133] Experimental Example 9: Intrinsic Viscosity Experiment The method for measuring intrinsic viscosity is to measure the aqueous solution to be measured according to the concentration, calculate the reduced viscosity, and extrapolate this to read the reduced viscosity at a concentration of 0, which is called the intrinsic viscosity. As mentioned above, the intrinsic viscosity refers to the volume per unit mass of the polymer when there is no interaction between polymer chains in the solvent.
[0134] The 0.5 (w / v)% aqueous solution of hyaluronic acid sodium salt prepared is diluted with distilled water to concentrations of 0.3 (w / v), 0.1 (w / v), 0.05 (w / v), 0.01 (w / v), and 0.005 (w / v). The viscosity is measured at 25°C using a Brookfield viscometer DV2T, which is calculated as the reduced viscosity and extrapolated to obtain the intrinsic viscosity. In the case of hyaluronic acid sodium salt having a molecular weight of 1.2 million, the reduced viscosity is calculated as 2.3 m. 3 In the case of sodium hyaluronic acid having an intrinsic viscosity of 1.8 m / kg and a molecular weight of 900,000, 3 / kg.
[0135] The sodium hyaluronic acid salt having a molecular weight of 1.2 million that passed through the column filled with silica prepared in Example 1 had a molecular weight of about 1.15 ml. 3Sodium hyaluronate having an intrinsic viscosity of about 0.8 m / kg and a molecular weight of 900,000 is 3 The intrinsic viscosity was calculated to be 1.0 g / kg.
Claims
1. It is a structure derived from high molecular weight hyaluronic acid, The structure is a polymeric hyaluronic acid structure characterized in that it has a single polymer chain.
2. 2. The polymeric hyaluronic acid structure according to claim 1, wherein the single polymer chain forms an ionic aggregate.
3. 3. The polymeric hyaluronic acid structure according to claim 2, wherein the ion association has a spherical structure having a diameter of 1 to 20 nm.
4. The molecular weight of the polymeric hyaluronic acid is 5.0×10 4 ~5.0×10 6 The polymeric hyaluronic acid structure according to claim 1, characterized in that its molecular weight is in the range of g / mol.
5. 2. The polymeric hyaluronic acid structure according to claim 1, wherein the structure is produced by applying shear stress to a solution containing hyaluronic acid, which is a precursor of the structure.
6. 6. The polymeric hyaluronic acid structure according to claim 5, wherein the shear stress is applied by passing a solution containing hyaluronic acid, which is a precursor of the structure, through a column packed with silica.
7. 6. The polymeric hyaluronic acid structure according to claim 5, wherein the shear stress is applied by passing a solution containing hyaluronic acid, which is a precursor of the structure, through one or more filter papers.
8. 8. The polymeric hyaluronic acid structure according to claim 7, wherein the filter paper is arranged by laminating two or more filter papers.
9. 6. The polymeric hyaluronic acid structure according to claim 5, wherein the shear stress is applied by applying ultrasonic waves to a solution containing hyaluronic acid, which is a precursor of the structure.
10. The solution containing the structure is 5.0 × 10 4 ~5.0×10 6 The polymeric hyaluronic acid structure according to claim 1, characterized in that the viscosity of a solution containing the structure is 10-700 cP when the structure has a molecular weight of g / mol and a concentration of 0.1-2.0%.
11. When the molecular weight and concentration of the structure and the hyaluronic acid precursor of the structure are the same, The polymeric hyaluronic acid structure according to claim 1, characterized in that the ratio of viscosity (a) of a solution containing the structure to viscosity (b) of a solution containing hyaluronic acid, which is a precursor of the structure, a / b, is 0.10 to 0.
99.
12. 2. The polymeric hyaluronic acid structure according to claim 1, wherein the contact angle of a solution containing the structure is 20° to 30° on a hydrophilic glass surface.
13. 2. The polymeric hyaluronic acid structure according to claim 1, wherein the contact angle of a solution containing the structure is 80° to 100° on a hydrophobic glass surface.
14. The intrinsic viscosity of the solution containing the structure is 0.1 to 2.0 m 3 2. The polymeric hyaluronic acid structure according to claim 1, wherein the polymeric hyaluronic acid structure has a molecular weight of 1000 to 15000 / kg.
15. A cosmetic composition comprising the polymeric hyaluronic acid structure according to claim 1.
16. 16. The cosmetic composition according to claim 15, wherein the cosmetic composition is formed in any one form selected from the group consisting of skin lotion, skin softener, skin toner, astringent, lotion, milk lotion, moisture lotion, nourishing lotion, massage cream, nourishing cream, moisture cream, hand cream, essence, nourishing essence, pack, soap, shampoo, cleansing foam, cleansing lotion, cleansing cream, body lotion, body cleanser, emulsion, pressed powder, loose powder, and eye shadow.
17. A method for producing a polymeric hyaluronic acid structure, comprising the steps of: A method for producing a polymeric hyaluronic acid structure, characterized in that the polymeric hyaluronic acid structure is produced by applying shear stress to a solution containing hyaluronic acid, which is a precursor of the structure.
18. 18. A method for producing a polymeric hyaluronic acid structure according to claim 17, characterized in that the shear stress is applied by passing a solution containing hyaluronic acid, which is a precursor of the structure, through a column packed with silica.
19. 18. The method for producing a polymeric hyaluronic acid structure according to claim 17, characterized in that the shear stress is applied by passing a solution containing hyaluronic acid, which is a precursor of the structure, through one or more filter papers.
20. 18. The method for producing a polymeric hyaluronic acid structure according to claim 17, wherein the shear stress is applied by applying ultrasonic waves to the hyaluronic acid that is a precursor of the structure.
Citation Information
Patent Citations
Purification of hyaluronic acid
JP1990103204A
Production of aqueous solution of sodium hyaluronate
JP1992158796A
Pharmaceutical products consisting of salts of hyaluronic acid with local anesthetics
JP2001503042A
Purification method for hyaluronic acid and / or salt thereof
JP2011195611A
Sterile hyaluronic acid solution
JP2013518926A